Analysis of Eddy‐Current Losses in Solid Iron Under dc‐Biased Magnetization Considering Minor Hysteresis Loops. Issue 3 (August 2014) - Shima, Kazuo; Fukami, Tadashi; Miyata, Kenji; Lee, Chahn; Furukawa, Yoko
SUMMARY In designing solid‐pole synchronous machines, it is important to take into account the surface eddy‐current losses in the field pole cores. In this study, a solid‐iron ring specimen is adopted as an approximate model of solid‐pole surfaces in order to conduct a fundamental study of the surface losses. The influence of the minor hysteresis loops on the losses under dc‐biased magnetization is investigated. The losses in the ring under dc‐biased magnetization are measured and analyzed by finite element analysis (FEA). The losses computed by the FEA considering minor loops are nearly the same as those measured. In contrast, the eddy‐current losses computed by FEA without considering minor loops are considerably inaccurate because the incremental permeability is overestimated and the skin depth is underestimated. It is important to consider hysteresis for the accurate calculation of the surface eddy‐current losses under dc‐biased magnetization.